THE USE OF POLITENESS STRATEGIES MANAGING ROMANTIC CONFLICTS CONTEXT IN BRIDGERTON’S NETFLIX SERIES (2020) - Sugita, Nabila Meidy (Language Horizon: Journal of Language Studies, 2024)
Romantic conflicts can be managed with the use of politeness strategies. Therefore, this study was carried out to investigate the usage of politeness strategies performed by main male and female characters in Bridgerton’s Netflix Series (2020) while dealing with romantic conflicts. The aims of this present study are at identifying the types of politeness strategies employed by main male and female characters in Briedgerton’s Netflix Series (2020) and revealing politeness strategies impact romantic conflicts of main male and female characters in Bridgerton’s Netflix series (2020). In order to conduct this study, this study adapted theory of politeness strategies proposed by Brown and Levinson (1987) and conflict resolution strategies as proposed by Sillars et al (1983). The method applied was a descriptive qualitative method since the data were in the forms of utterances and being identified descriptively based on the theory adapted. This recent study found that all types of politeness strategies employed by main male and female characters in Bridgerton’s Netflix series (2020) while dealing with romantic conflicts. This research revealed that there are differences regarding Simon and Daphne applying types of politeness strategies. Other than that, positive politeness is mostly employed to actualize cooperative strategy in dealing with romantic conflicts. Furthermore, in applying competitive strategy in dealing with romantic conflict, main male and female characters preferred adapting off-record. The least strategy in solving romantic conflicts used by main male and female characters is that avoidance strategy. This strategy can be done with mostly negative politeness.